Harry Potter and the Order of the Phoenix - Rowling, J. K. (Rowling, J. K. Harry Potter series, 2003)
When the government of the magic world and authorities at Hogwarts School of Witchcraft and Wizardry refuse to believe in the growing threat of a freshly revived Lord Voldemort, fifteen-year-old Harry Potter finds support from his loyal friends in facing the evil wizard and other new terrors.